Design and fabrication of lamp stationery rack / Tengku Ammer Aizad Tengku Sulaiman - Tengku Sulaiman, Tengku Ammer (2022)
The notion of product creation is thriving daily in the realm of modern technology in an effort to satisfy college students. Products with several features have significantly altered the modern world. These goods serve as both an excellent indicator of the advancement of product development and a dependable tool for making college students daily lives easier. Today, college students are more inclined to purchase a product with several features in addition to its attractive appearance. Considering college students aspiration as a focal point, this paper will develop a concept of multipurpose lamp stationery rack. The improved lamp stationery rack will provide a facility of certain number of products. This paper shows the construction of a multipurpose lamp stationery rack by gathering knowledge from college students and expert consultations. Various product development tools have been used to implement the desired concepts. Finally, an economic analysis has been shown to justify the feasibility of the product in production